Sustainable Water Management for Small Farmers with Center-Pivot Irrigation: A Hydraulic and Structural Design Perspective - Rashid M.; Haider S.; Masood M.U.; Pande C.B.; Tolche A.D.; Alshehri F.; Costache R.; Elkhrachy I. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In Pakistan, surface water supply for irrigation is decreasing, while water demand is increasing for agriculture production. Also, due to the fast rate of population growth, land holding capacity is decreasing. So, there is a need to develop appropriate technologies and design approaches for small-scale farmers to improve modern irrigation practices. In this study, a hydraulic and structural layout of CPIS was designed for small-scale farmers with some modifications. The hydraulic parameters and structural design of the CPIS were designed using IrriExpress and SAP2000 software, respectively. An economic analysis of the modified CPIS was carried out. The results revealed that in one complete revolution of the whole system, its span slope varied from 2.98 to 0.1%, and the wheel slope varied from 2.35 to ?2.4%. The timing setting was 60% for one revolution, and the irrigation depth was 10 mm. When the time setting was reduced from 100% to 10%, the irrigation hours per cycle and irrigation depth both increased. Variendeel type-II trusses were designed for structural purposes using SAP2000 software. This design led to a 17% reduction in weight by lowering it from 1.916 to 1.5905 tons and a 44% reduction in joint count, decreasing it from 32 to 18. Our economic analysis revealed that the structural part of the system is more expensive than the hydraulic, electric and power parts for small-scale design. So, it was suggested that CPIS is suitable for land holdings from 100 to 250 acres, because when the area increases to more than 250 acres, there is no significant change in the cost. A towable system is more economical for small-scale farmers due to its lower cost per acre. This study will be helpful for the optimization of CPISs to improve water use efficiency and crop yield. 2023 by the authors.